The Effect of Experience to the Accuracy of Giving Opinion with Audit Expertise, Professional Skeptisism, Audit Judgment as Mediators - Nugraha, Asa Septa; Suryandari, Dhini (Universitas Negeri Semarang, 2018)
This study aims to examine the role of audit expertise, professional scepticism and audit judgment in mediating the influence of experience on the accuracy of opinion by public accountants. The population in this study is the auditor at the Public Accounting Firm in the Semarang city as many as 17 firm with a population of 255 auditors. The sampling technique uses convenience sampling. The number of samples that can be processed by 55 respondents. Methods of data analysis uses descriptive analysis, multiple linear analysis and simple, and test sobel. Research study show that experience, audit expertise, and audit judgment have a direct effect on the accuracy of opinion and professional scepticism has no effect on the accuracy of opinion, experience influencing audit expertise, professional scepticism and audit judgment. Audit expertise and audit judgment capable of mediating the influence of experience on the accuracy of opinion and professional scepticism are unable to mediate the influence of experience on the accuracy of opinion. The conclusion of this research is that experience, audit expertise, and audit judgment will result in more accurate audit opinion and audit expertise and audit judgment can strengthen the influence of experience on accuracy of audit opinion